Urinary Levels of SARS-CoV-2 Nucleocapsid Protein Associate With Risk of AKI and COVID-19 Severity: A Single-Center Observational Study - Tampe, Désirée; Hakroush, Samy; Bösherz, Mark-Sebastian; Franz, Jonas; Hofmann-Winkler, Heike; Pöhlmann, Stefan; Kluge, Stefan; Moerer, Onnen; Stadelmann, Christine; Ströbel, Philipp; Winkler, Martin Sebastian; Tampe, Björn (Frontiers in Medicine, 2021)
Background: Acute kidney injury (AKI) is very common in severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) disease 2019 (COVID-19) and considered as a risk factor for COVID-19 severity. SARS-CoV-2 renal tropism has been observed in COVID-19 patients, suggesting that direct viral injury of the kidneys may contribute to AKI. We examined 20 adult cases with confirmed SARS-CoV-2 infection requiring ICU supportive care in a single-center prospective observational study and investigated whether urinary markers for viral infection (SARS-CoV-2 N) and shedded cellular membrane proteins (ACE2, TMPRSS2) allow identification of patients at risk for AKI and outcome of COVID-19. Objectives: The objective of the study was to evaluate whether urinary markers for viral infection (SARS-CoV-2 N) and shedded cellular membrane proteins (ACE2, TMPRSS2) allow identification of patients at risk for AKI and outcome of COVID-19. Results: Urinary SARS-CoV-2 N measured at ICU admission identified patients at risk for AKI in COVID-19 (HR 5.9, 95% CI 1.4–26, p = 0.0095). In addition, the combination of urinary SARS-CoV-2 N and plasma albumin measurements further improved the association with AKI (HR 11.4, 95% CI 2.7–48, p = 0.0016). Finally, combining urinary SARS-CoV-2 N and plasma albumin measurements associated with the length of ICU supportive care (HR 3.3, 95% CI 1.1–9.9, p = 0.0273) and premature death (HR 7.6, 95% CI 1.3–44, p = 0.0240). In contrast, urinary ACE2 and TMPRSS2 did not correlate with AKI in COVID-19. Conclusions: In conclusion, urinary SARS-CoV-2 N levels associate with risk for AKI and correlate with COVID-19 severity.